Effect of SME Food Entrepreneurs Knowledge on Halal Certification for Certified Awareness Using Partial Least Square - Giyanti, Ida; Indriastiningsih, Erna (Jurnal Teknik Industri, 2019)
This study aims to predict the impact of the understanding of halal certification by Small Medium Enterprise (SME) entrepreneurs on the intention to conduct halal certification. This study was conducted in the Cooperative and SME Office of Surakarta City. The Halal Certification Comprehension Rate was assessed using three variables.   We had knowledge of halal (PGT), perceived halal certification advantages (MNF), and perceived halal certification procedures (PROS).  Structural Equation Model-Partial Least Squares (SEM-PLS) was used for data analysis.  The results show that SMEs have a good knowledge of halal and agree that halal certification is beneficial to their businesses.  We found, though, that the processes for handling Halal Certification are relatively complex. Based on the study, the perception of Halal Certification Benefits (MNF) is significantly affected by the intention of SMEs to conduct Halal Certification (NHL). The other two results show a positive correlation. However, they are not statistically significant.This study aims to predict the impact of the understanding of halal certification by Small Medium Enterprise (SME) entrepreneurs on the intention to conduct halal certification. This study was conducted in the Cooperative and SME Office of Surakarta City. The Halal Certification Comprehension Rate was assessed using three variables.   We had knowledge of halal (PGT), perceived halal certification advantages (MNF), and perceived halal certification procedures (PROS).  Structural Equation Model-Partial Least Squares (SEM-PLS) was used for data analysis.  The results show that SMEs have a good knowledge of halal and agree that halal certification is beneficial to their businesses.  We found, though, that the processes for handling Halal Certification are relatively complex. Based on the study, the perception of Halal Certification Benefits (MNF) is significantly affected by the intention of SMEs to conduct Halal Certification (NHL). The other two results show a positive correlation, but they are not statistically significant.